(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the effect of Diaphragmatic breathing exercise on pain, anxiety, and depression in patients undergoing total knee replacement.Material and Methods: It is a randomized controlled trial. The study population consisted of patients who underwent total knee replacement surgery in the orthopedic ward of Çankırı State Hospital between May and August 2019. The study sample included a total of 38 patients satisfying the inclusion criteria. Stratified randomization was used to assign the patients into sex-matched intervention group (n=19) and control group (n=19). Patients in the intervention group were also trained in the Diaphragmatic breathing exercise procedure. Descriptive characteristics form, visual analogue scale and hospital anxiety and depression scale were used to collect data. Pain scores were evaluated at 1, 2, 4, 8, 12, and 24 hours postoperatively, while the anxiety and depression was applied on the postoperative day 2. Data were analyzed using descriptive statistics, Chi-square test, and Mann–Whitney U test. Results: Mean age was 65.26±6.73 years in the intervention group and 68.78±5.88 years in the control group. There were also no significant differences in Visuel Analog Scale pain scores (P>.05). Mean score anxiety was significantly lower in the intervention group compared to the control group (P=.033). However, the difference in the depression was not significant (P>.05). Conclusion: The results of our study demonstrated that Diaphragmatic breathing exercise had no effect on pain and depression but reduced anxiety after total knee replacement surgery.